Service turnover structures in selected Central European countries between 2015–2021 : An analysis - Niewiadomski, Michał; Niemczyk, Agata; Zamora, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Services constitute an important part of the economy. From an economic development standpoint, one of the most meaningful groups is high technology services. This study diagnoses changes of turnover in services structure. The spatial scope covers Central and Eastern European countries, the time range — the years 2015–2021. The article is theoretical and analytical in nature. Research methods typical for this type of studies were used: critical literature of the subject analysis and investigation of published empirical secondary data conducted with decision tree method.
Keywords: high technology services; COVID-19; Central and Eastern Europe